Measuring connectivity patterns in a macro-corridor on the south coast of Western Australia - Dunn, Adam; Majer, Jonathan (Blackwell Publishing Asia, 2009)
Portions of the south coast of Western Australia are recognized as environmentally valuable because of high levels of biodiversity, but are at risk due to continued anthropogenic influences, particularly in the form of fragmentation and habitat loss. Corridors of habitat, either continuous or stepping-stone, are deemed to be valuable for the maintenance and increase of biodiversity in the region. Here we apply a series of betweenness centrality analyses to quantify the connectivity in the region. The method we describe here is an extended application of the betweenness centrality measure, which is a measure of spatial connectivity that is applied to fragmented landscapes. The method is used for significant corridors between the Stirling Ranges and the Fitzgerald River National Park to identify a series of locations that are important to the connectivity in this region and thus may provide effective locations for restoration inputs.